Crisis in scientific research funding in Brazil: What are the impacts in Sports and Leisure's field? - Maria Clara Elias Polo; Giselle Helena Tavares (Universidade Salgado de Oliveira, 2020)
This documental study aimed to analyze the projects approved with funding by CNPq, related to Leisure and Sports, in the Physical Education area of knowledge and other Major Areas. Approved projects were analyzed from the period 2012 to 2016 in the Universal Public Notice. The search terms used were "leisure", "sport", "physical activity", " exercise". Method Content Analysis was used. Between these years, only 10 projects were approved with the term Leisure and 30 with the term Sport. In other fields, 21 projects with the term Leisure and 16 projects with Sport were approved. In conclusion, there are few studies in leisure and sport's field with funding, evidencing the negligible investment in the socio-cultural and pedagogical sub-areas related to Leisure and Sports.